2020
DOI: 10.1016/j.jstrokecerebrovasdis.2020.105106
|View full text |Cite
|
Sign up to set email alerts
|

Weekend Effect on in-Hospital Mortality for Ischemic and Hemorrhagic Stroke in US Rural and Urban Hospitals

Abstract: Introduction: Previous studies have reported a "weekend effect" on stroke mortality, whereby stroke patients admitted during weekends have a higher risk of in-hospital death than those admitted during weekdays. Aims:We aimed to investigate whether patients with different types of stroke admitted during weekends have a higher risk of in-hospital mortality in rural and urban hospitals in the US. Methods:We used data from the 2016 National Inpatient Sample and used logistic regression to assess in-hospital mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“… 6 , 7 With an increasing number of patients with PAD admitted to the hospital, there is an urgent need to optimize treatment to improve clinical outcomes and reduce mortality for patients with PAD. The in‐hospital mortality in the United States among patients hospitalized with PAD was reported as being from 2.5% to 3.1% in the literature, 8 , 9 which was similar to in‐hospital mortality for patients with acute ischemic stroke (2.3% to 4.2%) 10 and slightly lower than that among patients with an acute myocardial infarction (4.6%). 11 Studies have reported that patients hospitalized for PAD with anemia, 12 chronic kidney disease, 13 atrial fibrillation, 14 and patients who underwent major lower extremity amputation 15 had higher risk for in‐hospital mortality.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“… 6 , 7 With an increasing number of patients with PAD admitted to the hospital, there is an urgent need to optimize treatment to improve clinical outcomes and reduce mortality for patients with PAD. The in‐hospital mortality in the United States among patients hospitalized with PAD was reported as being from 2.5% to 3.1% in the literature, 8 , 9 which was similar to in‐hospital mortality for patients with acute ischemic stroke (2.3% to 4.2%) 10 and slightly lower than that among patients with an acute myocardial infarction (4.6%). 11 Studies have reported that patients hospitalized for PAD with anemia, 12 chronic kidney disease, 13 atrial fibrillation, 14 and patients who underwent major lower extremity amputation 15 had higher risk for in‐hospital mortality.…”
mentioning
confidence: 61%
“…PAD is a major health care problem, and this condition has a high mortality during hospitalization when compared with ischemic stroke. 10 Using the NIS 2016 to 2019, we identified all patients admitted to the hospital primarily because of the PAD diagnosis. ML models were established to predict in‐hospital mortality and reveal important risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…For more than 20 years, the term “weekend effect” has been used by the medical community to describe the higher mortality rate for hospitalizations occurring on weekends versus weekdays [ 3 ]. This effect has been recognized in the fields of cancer, pulmonary embolism, and stroke [ 2 , 13 ]. Several studies examined the weekend effect in ischemic stroke requiring endovascular MT.…”
Section: Discussionmentioning
confidence: 99%
“…Based on 2016 National Inpatient Sample data, a United States study did not observe a relationship between mortality and admission day among AIS patients with rural–urban diversity, which was attributed to updated investigations and the efforts of modern stroke care quality promotion ( 31 ). A study reported that rural AIS patients treated in hospitals in agricultural regions had similar benefits and safety from thrombolytic treatment in Portland and even had a lower chance of intravenous thrombolysis at night, and improvements in telecommunication and patient transport from rural areas during the night weakened the weekend effect ( 47 ).…”
Section: Discussionmentioning
confidence: 99%